McDowell's oscillation, objectivity and rationality - Garner, S; Stephanie Garner (2010)
﻿ Mind and World is written in a Wittgensteinian spirit. It is a work whose aim is to address a specific philosophical discomfort. John McDowell diagnoses a tension between the urge for what he describes as 'minimal empiricism' and its apparent impossibility. Minimal empiricism is defined as the idea that constraint is exercised on our thought by the world through experience. In his view, minimal empiricism stands in tension with the fact that conceptually unstructured impressions can have no rational bearing on our beliefs and judgements. This tension forces an oscillation between two equally unattractive positions: the Myth of the Given and coherentism. McDowell's aim is to dissolve this apparent tension which he sees as resting on the more basic assumption of a dualism between reason and nature. Through his invocation of 'second nature' he aims to present a naturalised Platonism in which man's occupation of the space of reasons can be seen as an aspect of his animal nature, not as something essentially alien to us. The thesis starts by outlining McDowell's attempt to escape the oscillation he detects between the Myth of the Given and coherentism. In Chapter One, the content of Mind and World is briefly laid out. The underlying dualism of reason and nature on which the oscillation is said to rest is considered and the resources he employs in his attempt to escape it discussed. These resources include his metaphysical rejection of sideways-on accounts of understanding. The second chapter reinforces the first by isolating and defining a number of key concepts in McDowell's picture. The material discussed here is largely drawn from works other than Mind and World. Three key assumptions are isolated: the rejection of sideways-on accounts of understanding, the de re nature of singular thought and the fully conceptual nature of experience. These assumptions are shown to play a pivotal role in his philosophy by considering his work on Aristotle and Descartes. McDowell aims to provide a 'therapeutic dissolution' of the oscillation between the Myth of the Given and coherentism. In order to be successful it must meet (at least) three criteria which emerge from his writings. These criteria are discussed alongside attempts by other philosophers to escape the oscillation that McDowell detects. The third chapter develops, in broad outline, the argument of the thesis. Two lines of thought are traced from the three central elements of McDowell's view identified in the second chapter. The first stems from his rejection of sideways-on accounts of understanding, whilst the second arises from the object-dependence of singular thought. The picture in Mind and World incorporates what Julian Dodd has termed a 'modest identity theory of truth'. Put simply, an identity theory states that facts are true propositions, and the theory is modest if facts are taken to be composed of senses. McDowell himself explicitly accepts that his picture is committed to a modest identity theory, though its exact nature is unclear from his writings. McDowell's semantic externalism appears to provide an account in which singular senses are object-dependent. Thoughts are composed of these senses, and so are dependent on objects in the world for their content. One would expect that facts too (which are true possible thoughts) would be object-dependent. After all they are composed of object-dependent entities, namely senses. Such a position encourages the idea that objects are explanatorily independent of facts. In Kit Fine's terminology, propositions about objects 'ground' propositions about senses. However, this idea stands in tension with McDowell's rejection of sideways-on accounts of understanding. He claims that the world is composed of facts and that reality does not exist beyond the conceptual realm. Such a position suggests that objects exist only derivatively from their role in facts: "objects figure in the world by figuring in facts, which are true thinkables" [McDowell (1999a) p94. My italics]. In other words, that propositions about facts 'ground' propositions about objects. Since 'grounding' is an asymmetric notion, there is a tension in McDowell's picture which needs to be resolved. Chapter Four examines McDowell's Kantian account of objects. Objects are derived from facts. McDowell is not committed to a substantial semantic externalism in which, when we investigate whether our terms have a reference, we look at the world to see whether there is an object corresponding to our sense of the term. Instead, McDowell's semantic externalism is truistic: once a sense appears in a fact, no further questions can be asked about the reference of the term. The sense's figuring in a true possible thought ensures that there is a reference. There can be no sense without reference because objects are derived from facts (which are true possible thoughts). The conception of objects that McDowell offers, however, fails to sustain important common-sense realist intuitions. Looked at as an account of empirical objects (rather than formal objects, such as mathematical ones), there are deficiencies which can be brought out. His account can be challenged on the grounds that it is unable to allow that sapient and sentient environments have a common ontology. The discussion is framed as a dialogue between a common-sense realist and a McDowellian thinker. This provides for responses to the reasoning to be considered at every appropriate point. These responses are, in the end, not sufficient to allow his account to meet the realist intuitions. He has therefore failed to provide an account based on mere reminders of common-sense truisms. His account of objects is revisionary and must be either replaced or defended by positive arguments. The quietist's claim that only negative arguments are needed to defend his position is undermined once the position abandons common-sense realism. In Chapter Five the focus shifts back to the overall argument laid out in Chapter Three. It might be thought that McDowelPs particular conception of objects is a peripheral error. If this were the case, since his basic account has not been shown to abandon common-sense realism, his revisionary conception of objects could simply be dropped. This line of thought is countered. I present the arguments of two commentators to show the strength of my objection. Mark Sainsbury argues that McDowell should not maintain a substantial form of semantic externalism if he stands firm to his rejection of sideways-on accounts of understanding. Ruth Millikan argues that McDowelPs commitment to a substantial form of semantic externalism stands in tension with his account of sense, which is a central element in his rejection of sideways-on accounts of understanding. The tension which concerns these commentators needs to be addressed. The conception of objects considered in Chapter Four is required. It provides McDowell's explanation of how his rejection of sideways-on accounts of understanding is consistent with his semantic externalism. The final chapter concludes the argument of the thesis. It is shown that McDowell's theory (as it stands) fails to meet his therapeutic aspirations. In particular he has failed to meet two of the three therapeutic requirements attributed to him in Chapter Two. His conception of objects is revisionary and his picture does not avoid the appearance of an insurmountable problem in world-directed thoughts. Its failure to provide for common-sense realism means that he can no longer avail himself of the quietist strategy which disavows the need to provide positive arguments for its conclusions. Therapeutic dissatisfaction with his picture is the result. The argument of this thesis is then located within a broader philosophical landscape. Since my argument unsettles the quietist position it provides a platform from which to launch other criticisms. McDowell has frequently rejected the arguments of other philosophers on the basis that they suggest he needs to positively argue for his picture. Once his right to maintain this line of response is undermined, their objections can then be applied successfully. In particular, if my argument is successful then the objections launched against the 'moderate Platonist' by William Child can now be effectively deployed against McDowell's picture. The objections of two other commentators, Robert Brandom and Crispin Wright, will also be considered. Considering his responses to their objections reveals that he has no obvious resources to maintain his view, once his right to the quietist insistence that common-sense is the 'default' position has been undermined by my argument.